HLA-C Alleles and Cytomegalovirus Retinitis in Brazilian Patients with AIDS - Biberg-Salum, Tania Gisela; Veronese Rodrigues, Maria de Lourdes; Morais Fernandes, Ana Paula; Deghaide, Neifi Hassan Salum; Paula, Jayter Silva de; Castelli, Erick C. [UNESP]; Mendes-Junior, Celso Teixeira; Donadi, Eduardo Antonio (Hindawi Ltd, 2018)
Purpose. Since cytomegalovirus retinitis (CR) is an important cause of visual impairment among AIDS patients and HLA-C alleles have been associated with AIDS disease outcome, we typed HLA-C locus in patients with AIDS exhibiting or not CR. Methods. Three groups of individuals were studied: (i) 49 patients with AIDS and CR (Group I), (ii) 161 patients with AIDS without CR (Group II), and (iii) 202 healthy HIV-negative individuals (Group III). HLA-C typing was performed using commercial kits. Results. The H LA-C*07 allele group was underrepresented in AIDS patients with CR (P = 0.005) when compared to controls or when compared to AIDS patients without CR (P = 0.006). The IILA-C*05 allele group was overrepresented in Group II in comparison to Group III (P = 0.017). The frequency of the HLA-C* 16 allele group was increased in Group III in comparison to Group II (P = 0.004). Conclusion. The HLA-C*07 allele group conferred protection against the development of CR in Brazilian AIDS patients, whereas the HLA-C*05 and HLA-C*16 allele groups were associated with AIDS susceptibility or protection, respectively.